Efficacy of pre-participation cardiac evaluation recommendations among athletes participating in World Athletics Championships. (1st September 2020) - Dahlström, Örjan; Adami, Paolo Emilio; Fagher, Kristina; Jacobsson, Jenny; Bargoria, Victor; Gauffin, Håkan; Hansson, Per-Olof; Andersson, Christer; Bermon, Stéphane; Timpka, Toomas
Abstract : Background: Athletes competing in athletics (track and field) at international level may be participating with underlying undiagnosed life-threatening cardiovascular conditions. Our objective was to analyse variations in pre-participation cardiac evaluation prevalence among athletes participating in two International Association of Athletics Federations (IAAF) World Athletics Championships, with regard to the human developmental level and global region of their home countries, as well as athletes' age category, gender, event group and medical insurance type. Design: Cross-sectional web-based survey. Methods: A total of 1785 athletes competing in the IAAF World Under 18 Championships Nairobi 2017 and World Championships London 2017 were invited to complete a pre-participation health questionnaire investigating the experience of a pre-participation cardiac examination. Results: A total of 704 (39%) of the athletes participated. Among these, 59% (60% of women; 58% of men) reported that they had been provided at least one type of pre-participation cardiac evaluation. Athletes from very high income countries, Europe and Asia, showed a higher prevalence of at least one pre-participation cardiac evaluation. Conclusions: The prevalence of pre-participation cardiac evaluation in low to middle income countries, and the African continent in particular, needs urgent attention. Furthermore, increases in evaluation prevalence should be accompanied by the development of cost-effective methods that can be adopted in all global regions.